Outer Children Marriages Status After Constitutional Court Decision No: 46/PUU-VII/2010 - Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2014)
The decision of the Constitutional Court of the Republic of Indonesia No.46/PUU-VIII / 2010 dated 17 February 2012, granted the judicial review of Article 43 (1) of Law No. 1 of 1974 on Marriage by deciding that the article should read